Psychological Analysis of Fatih’s Character-Building in Egosentris: A Novel by Syahid Muhammad - Nursafira, Mutia Sari; Putri, Wella Cisilya; Yunira, Sandra; Gari, Nelia; Hamuddin, Budianto (Elsya : Journal of English Language Studies, 2019)
As current era necessitates access to information technology, people of all ages are exposed to the prevalent online hate speech. This literature analysis aims to analyse the psychological characterisation of Fatih, one of the characters in Syahid Muhammad’s novel Egosentris, to address how current social media interactions negatively affects one’s mental health. This article described characterisation and psychological conflict using the literary psychology approach based on Sigmund Freud's psychoanalytic theory, in line with the characterisation theory proposed by Nurgiyantoro (2007). Psychoanalytic theory is a staple theory of human personality that is often used in the world of literature, which is divided into three structures of human nature, i.e., id, ego, and superego. The analysis involved several steps, such as categorisation, tabulation, interpretation, inference, and validity of the data. The results of the study revealed that Fatih's personality in the Egosentris novel is kind, honest, sensitive, critical, and caring. Though in some situations, Fatih's character was found to employ some negative characters such as being stubborn, spiteful and bad-tempered. This present article also found the psychological conflict experienced by Fatih includes emotions such as anger, anxiety, fear, regret, pressure, and resentment. These kinds of psychological conflict have changed his personality to be an inclusive person. The study reflects the outcomes of psychological analysis on Fatih’s character to raise public awareness about regarding importance of noticing people’s mental health and to diminish the spread of hate comments and harmful speech to others.